Das areias da praia às areias da moradia:um embate socioambiental em Fortaleza - CE - Lima, Ernandy Luis Vasconcelos de (2005)
The knowledge of the geodynamic and social evolution constitues the essential analyze for the planning of the use and occupation, regarding the alterations of the human activities in the natural processes. It avoids futures environmental damages. The study area is located at Serviluz locality, Fortaleza County, Northeastern Brazil. The main objective is to define the environmental dynamics through the characterization of the aeolian dynamics in the transport of sediments in the Future and Serviluz beaches and of the analysis of the natural and social impacts caused the Serviluz locality population. The applied methodology was based on a systematic approach, using qualitative and quantitative data and analyzing the evolution of an environmental system starting from the geodynamics and social processes in the urban area occupation near the coast. Socio-environmental impacts are affecting the natural dynamics in the study area. Dune migration and aeolian sediments along the Serviluz coast are burying the houses, buildings, beach huts, access roads and the urban infrastructure. Besides, the greater part of community does not have the house's ownership because it occupied the area illegally in navy lands. Currently six thousand families, this place serves as a local for activities port, industrial and residential. So, a knowledge integrated for the environmental characterization was done for understanding of the socio-environmental impact verified in the study area, starting from the located connections in this place among the natural phenomena (coastal dynamics) and social aspects.